The Juridical Impact of the Implementation of the Paradigm Regarding the Determination of the National Capital (IKN) of the Archipelago as an Asymmetric Region - Ayyubi, Manggala; Perwira, Indra; Abdurrahman, Ali (JOELS: Journal of Election and Leadership, 2023)
The relocation of the National Capital (IKN) of the archipelago to Kalimantan reaped pros and cons from the community. However, as a democratic country, when the State has decided to move the National Capital (IKN) of the archipelago with a democratic process through law, all components of the nation should support it. The Indonesian nation needs to minimize the excesses of moving the National Capital (IKN) of the Archipelago. There is no single decision that satisfies all people, but decisions that provide greater benefits to the Indonesian nation must be supported as a form of love and devotion for the Unitary State of the Republic of Indonesia in 1945. The results showed that and obstacles in determining the National Capital (IKN) of the archipelago as an asymmetric area as described in the discussion were imbalance, injustice, regional conflicts, coordination and integration, resource management, inadequate infrastructure, availability of public services, uneven economic development, lack of investment and private sector development, complex interagency coordination, and social and cultural change. And there is no concrete case study regarding the implementation of the National Capital (IKN) of the archipelago as an asymmetric area because this plan is still in the planning and discussion stage.